Frequency and antibiotic resistance of bacteria implicated in community urinary tract infections in North Aveiro (2011-2014) - Costa, Tânia Alexandrina Ribeiro (2015)
The urinary tract infection is the second most common infection in community and the most common nosocomial infection worldwide. Specific subpopulations are more likely to have UTI, such as, infants, pregnant women, elderly, diabetics, patients with urologic abnormalities, patients with catheters and immunodeficients. All the samples were collected at Centro Médico da Praça Lda on ambulatory system, located in São João da Madeira municipality, District of Aveiro north (Portugal) from June 2011 to June 2014. From 4270 analysed urine samples, 3561 (83%) were collected from women and only 709 (17%) were collected from men, in a range age from 0 to 104 years old. E. coli was (64%) the most frequent uropathogen, followed by Klebsiella spp (12%), Enterococcus spp (7%) and P. mirabilis (6%). From all samples, 1537 (37%) were multidrug resistant (MDR), 1099 were from women and 437 from men. The MDR uropathogens were resistant on average to a 6 antimicrobials and to a 5 antimicrobial classes of drugs. In general, men were more resistant to antimicrobials than women. According the results of this study, among the first line drugs recommended by EUA for empirical treatment of UTI the antimicrobials only nitrofurantoin is suitable for both sexes and ciprofloxacin may be only considered to treat women. From EAU recommended second line therapy, ampicillin is not appropriated to empirical treatment for both sexes, amoxicillin-clavulanic acid and trimethoprim-sulfamethoxazole should not be considered for men UTI empirical treatment, due the local high incidence of resistance. Thus, it is suggested imipenem and gentamicin as alternatives to treat both sexes.